2013
DOI: 10.1111/liv.12285
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic steatosis in diabetic patients does not predict adverse liver‐related or cardiovascular outcomes

Abstract: Although steatosis on imaging is often the abnormality that triggers diagnosis and assessment of NAFLD/NASH, it lacks predictive value for adverse clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 21 publications
4
44
0
Order By: Relevance
“…In primary and secondary care facilities, simple serum biomarkers can help targeting patients with an established diagnosis of NASH who need expedited referral to tertiary care centers. In line with previous histologic and imaging studies, we also showed that non-invasive diagnostic tools for hepatic steatosis lack predictive value for clinical outcomes in patients with NASH [10,32,33]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In primary and secondary care facilities, simple serum biomarkers can help targeting patients with an established diagnosis of NASH who need expedited referral to tertiary care centers. In line with previous histologic and imaging studies, we also showed that non-invasive diagnostic tools for hepatic steatosis lack predictive value for clinical outcomes in patients with NASH [10,32,33]. …”
Section: Discussionsupporting
confidence: 90%
“…In a US community-based cohort study of 337 type 2 diabetic patients, a histologic or ultrasonographic diagnosis of NAFLD had a HR of 2.2 to predict overall mortality and NAFLD was associated with significantly higher mortality caused by liver disease and malignancy [13]. However, a study of 2342 type 2 diabetic patients concluded that steatosis >30% lacks predictive value for adverse clinical outcomes [33]. Our finding is in line with histologic paired biopsy studies which showed that steatosis alone is a weaker predictor for progressive NASH than liver fibrosis stage [32].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the emerging notion that simple steatosis secondary to NAFLD may not be associated with significantly increased risk of peripheral neuropathy or other diabetes specific complications but that NASH, in particular with fibrosis, is associated (Dunn et al, 2013;Kim, Kim, Kim, & Therneau, 2013;Kim, Jung, Mok, Kang, & Kim, 2014;Musso et al, 2014;Williams et al, 2013). Indeed, in regard to the relationship between peripheral neuropathy and steatosis on ultrasound, our data are consistent with a South Korean study that found no association (Kim et al, 2014).…”
Section: Discussionsupporting
confidence: 94%
“…Table 1 summarizes the retrospective and prospective studies that have assessed the relationship between NAFLD and the risk of CVD events and mortality [17,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Most of these studies support the assertion that CVD is the most common cause of mortality among patients with NAFLD.…”
Section: Nafld and Cvdmentioning
confidence: 86%
“…Regarding the imaging-diagnosed NAFLD [17,[26][27][28][29][30][31][32][33][34][35][36], several retrospective and prospective cohort studies have shown that NAFLD was associated with an increased incidence of major CVD events, independently of traditional risk factors and MetS traits. In contrast, and surprisingly, using data from the Third National Health and Nutrition Examination Survey database, the investigators…”
Section: Nafld and Cvdmentioning
confidence: 99%